PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA KULIAH KONSEP DASAR IPS DI PERGURUAN TINGGI - Laelia Nurpratiwiningsih; Prasetyo Yuli Kurniawan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Research objectives include; (1) analyze the needs of lecturers and students related to learning media, (2) produce learning media that is worth using in learning, and (3) know the effectiveness of interactive learning media basic concepts of IPS in higher education. This research is a development research by doing 7 stages. These stages are the stage of analysis of potential problems, information collection, product design, design validation, design revision, product creation and limited product trials. Research instruments are given to lecturers and students during the learning of basic concepts of IPS. Techniques in data collection used include interviews, documentation, observations, questionnaires, and tests. Data analysis techniques through media needs data analysis, validation test and product effectiveness test. The results showed that (1) Analysis of the needs of the basic concept learning media of IPS in universities is demonstrated by the results of materials and presentations delivered in full. (2) The development of interactive learning media in the basic concept course of IPS is feasible for students and lecturers in learning in higher education. (3) The maturity of interactive learning media is effective in IPS learning. This is seen from the results of his study showing that 0.001.